ORGANISATIONAL CHANGE: A CONCEPTUAL AND THEORETICAL REVIEW - Eleni ARAVOPOULOU (Nowoczesne Systemy Zarządzania, 2015)
The organisational change is a phenomenon which has gained attention from theoretists and practioners alike. The paper analyzes the notion of change, oragnizational change and types of change. The paper is of theoretical nature. Several authors have perceived organisational change as a “response” to an organisation’s internal and/or external environment. The paper investigates different perspectives of emergent change basing on Kanter et al., (1992) Kotter (1996) and Luecke (2003). The author highlights that these three models have some common features: a development of vision and leadership. On the other hand Strobel (2015) refutes the argument that there is “one best way” that can be applied in all situations and organisations, when managing change, and promotes the idea of “one best way” for each situation and organisation individually. Moreover the drivers and types of organizational change are presented. Several forces driving organisational change have been identified and they basically involve factors with regards to both the internal and external environment of an organisation.